2014
DOI: 10.1177/0265532214562099
|View full text |Cite
|
Sign up to set email alerts
|

The use of eye tracking in research on video-based second language (L2) listening assessment: A comparison of context videos and content videos

Abstract: Investigating how visuals affect test takers’ performance on video-based L2 listening tests has been the focus of many recent studies. While most existing research has been based on test scores and self-reported verbal data, few studies have examined test takers’ viewing behavior (Ockey, 2007; Wagner, 2007, 2010a). To address this gap, in the present study I employ eye-tracking technology to record the eye movements of 33 test takers during the Video-based Academic Listening Test (VALT). Specifically, I aim to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(61 citation statements)
references
References 42 publications
(101 reference statements)
2
38
0
4
Order By: Relevance
“…These authors recorded the participants while taking the tests and they measured the amount of time informants look towards the monitor. Suvorov (2015) uses eye-tracking technology to investigate how examinees interact with two types of videos: context videos and content videos. He discovers that test-takers spend 58% of the time watching content videos and 51% context videos.…”
mentioning
confidence: 99%
“…These authors recorded the participants while taking the tests and they measured the amount of time informants look towards the monitor. Suvorov (2015) uses eye-tracking technology to investigate how examinees interact with two types of videos: context videos and content videos. He discovers that test-takers spend 58% of the time watching content videos and 51% context videos.…”
mentioning
confidence: 99%
“…As for the video, there were mixed results: three participants expressed that when they saw the speaker's lip movements they comprehend the information better; two participants used gestures to alert them of topic changes; and four used facial gestures to understand the speaker's opinion about a topic. Suvorov (2014) Other studies that also have examined the impact of the use of video on listening performance have reported other results. Wagner (2007) reported that video is not a distraction and participants performed better on tests with video input.…”
Section: Originalmentioning
confidence: 97%
“…Por ejemplo, en el estudio de Ockey (2007) la media de observación es el 44.9% del tiempo, y en los de Wagner (2007Wagner ( , 2010b el 69% y el 47.9%, respectivamente. En un estudio reciente, Suvorov (2015) utiliza tecnología de seguimiento ocular para investigar la conducta visual en dos tipos de textos audiovisuales: context videos (lo visual proporciona información sobre la situación comunicativa) y content videos (la información visual está relacionada con la verbal). En el primer caso, los participantes ven el vídeo el 50.70% del tiempo y, en el segundo, el 57.99%.…”
Section: Impacto De La Imagen En La Comprensión Valoración De La Imaunclassified